2021
DOI: 10.1016/j.amsu.2021.102856
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative heart rate variability analysis is as a potential simple and easy measure for predicting perioperative delirium in esophageal surgery

Abstract: Background Delirium is one of the most common but severe perioperative complications. Autonomic activity evaluated by heart rate variability (HRV) has been recently reported as a useful tool for prediction and for early detection of delirium in acute care medicine, especially in postoperative intensive care unit (ICU) patients. We hypothesized that HRV, by 3-lead electrocardiogram (ECG), one day prior to surgery might correlate with the presence of postoperative delirium. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…We previously reported that preoperative HF is correlated with postoperative delirium in patients undergoing radical surgery for esophageal cancer [ 8 ]. The surgery for esophageal cancer is long and highly invasive, and the incidence of postoperative delirium was 23% [ 8 ]. A short-term preoperative HRV consistently predicts postoperative delirium across facilities and surgical sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that preoperative HF is correlated with postoperative delirium in patients undergoing radical surgery for esophageal cancer [ 8 ]. The surgery for esophageal cancer is long and highly invasive, and the incidence of postoperative delirium was 23% [ 8 ]. A short-term preoperative HRV consistently predicts postoperative delirium across facilities and surgical sites.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, delirium was diagnosed by CAM-ICU and not based on questionnaires from a psychiatrist. In the previous paper, we investigated the relationship between postoperative delirium and HRV in esophageal cancer surgery in the ICU, and delirium was diagnosed by psychiatrists [ 8 ]. Although this method is more popular because the ICU nurses evaluate during their working hours, unlike a psychiatrist's diagnosis, there is a high likelihood of overlooking low activity and reduced judgment accuracy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another heart rate variability analysis found that preoperative high-frequency power was signi cantly lower in delirium patients than in non-delirium patients. Preoperative measurement of heart rate variability may be a useful predictor of delirium [31] . Therefore, abnormal autonomic activity may also be one of the mechanisms of postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%
“…New sleep medications, ramelteon and suvorexant, have also been reported to have preventive and therapeutic effects [35][36][37] and are increasingly prescribed on regular basis rather than as-needed. At our institution, we hypothesized that heart-rate variability could be used to predict delirium, and we have found that changes in autonomic nerves on the day before surgery can help predict delirium [38].…”
Section: Author Detailsmentioning
confidence: 99%